2016
DOI: 10.3402/ecrj.v3.31802
|View full text |Cite
|
Sign up to set email alerts
|

Bronchoscopy as a supplement to computed tomography in patients with haemoptysis may be unnecessary

Abstract: BackgroundHaemoptysis is a common symptom and can be an early sign of lung cancer. Careful investigation of patients with haemoptysis may lead to early diagnosis. The strategy for investigation of these patients, however, is still being debated.ObjectivesWe studied whether the combination of computed tomography (CT) and bronchoscopy had a higher sensitivity for malignant and non-malignant causes of haemoptysis than CT alone.MethodsThe study was a retrospective, non-randomised, two-centre study and included pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 20 publications
4
28
3
Order By: Relevance
“…The haemoptysis Diagnostic Imaging Pathway that is endorsed by the Western Australian Department of Health only suggests CT chest in selected high risk patients and bronchoscopy only when CT does not identify a cause for symptoms [20]. This conservative approach to haemoptysis management is based on several studies that have shown the additional diagnostic yield for lung cancer from bronchoscopy is very low when thoracic imaging has not already demonstrated concerning findings [21][22][23]. The appropriate management of mediastinal and hilar lymphadenopathy without a parenchymal lung lesion is less clear.…”
Section: Discussionmentioning
confidence: 99%
“…The haemoptysis Diagnostic Imaging Pathway that is endorsed by the Western Australian Department of Health only suggests CT chest in selected high risk patients and bronchoscopy only when CT does not identify a cause for symptoms [20]. This conservative approach to haemoptysis management is based on several studies that have shown the additional diagnostic yield for lung cancer from bronchoscopy is very low when thoracic imaging has not already demonstrated concerning findings [21][22][23]. The appropriate management of mediastinal and hilar lymphadenopathy without a parenchymal lung lesion is less clear.…”
Section: Discussionmentioning
confidence: 99%
“…Its sensitivity for isolating the source of the bleeding is as high as 92%. 10 CT can help differentiate between a parenchymal versus vascular cause of bleeding if used in conjunction with intravenous contrast 10 (►Fig. 4).…”
Section: Computed Tomographymentioning
confidence: 99%
“…5 Chest CT scanning plays a crucial and complementary role to bronchoscopy in cases of hemoptysis, with an ability to identify the site, side, and cause of bleeding of up to 92%. 6 The superiority of chest CT scanning over bronchoscopy is explained by the fact that a CT scan can identify lesions in the lung parenchyma, as well as vascular abnormalities that cannot be visualized bronchoscopically. Recently, it has been suggested that chest CT scans could stand alone as the diagnostic workup in cases of nonmassive hemoptysis in the outpatient setting.…”
Section: Bronchoscopy Vs Ct Chest Scanmentioning
confidence: 99%
“…Recently, it has been suggested that chest CT scans could stand alone as the diagnostic workup in cases of nonmassive hemoptysis in the outpatient setting. 6 Bronchoscopy, however, is superior in diagnosing mucosal abnormalities in the central airways, is equivalent to a CT scan of the chest in localizing the site of bleeding, and perhaps most importantly, can provide a tissue-based diagnosis to guide further therapy. 7 Clearly, it is inadvisable to transport an unstable and actively bleeding patient to the CT suite unless a secure airway is in place.…”
Section: Bronchoscopy Vs Ct Chest Scanmentioning
confidence: 99%